34.9k views
1 vote
What if the following is the sum of both solutions of the equation....

What if the following is the sum of both solutions of the equation....-example-1

1 Answer

2 votes

answer

D 2

factor

factor the equation
x^(2) - 2x - 8 = 0 into (x + a) and (x + b) so that a + b = -2 and a * b = -8

the two numbers that meet these conditions are a = -4 and b = 2


x^(2) - 2x - 8 = (x - 4)(x + 2)

find solutions

set both (x - 4) and (x + 2) equal to zero to find your solutions

x - 4 = 0

x = 4

x + 2 = 0

x = -2

add solutions

since the two solutions are x = 4 and x = -2, add them together to get your final answer

4 + (-2) = 2

User Dbajtr
by
5.3k points